(untitled) (American Journal of Islam and Society, 1994)
This seminar, organized by the Asian Institute for Development Communication in collabomtion with the Asia Foundation, was attended by thirty journalists and media professionals from Malaysia. Among the resource persons were Mochtar Lubis (Chairman, Press Foundation of Asia) and S. M. Ali (Chief Editor, Daily Star, Bangladesh). The seminar was opened by Riley Haji Jeffrey (Deputy Minister of Information, Malaysia), who discussed the importance and the need for development journalism to achieve the goal of Vision 2020 (i.e., becoming a fully "developed country" by 2020). He said that "mass media should not deprive people of in-depth analysis or exposition of issues in the social, economic, cultural , and environmental fields." James R. Klein (Representative, Asia Foundation) analyzed the complementary roles of editors and journalists in fulfilling the objectives of development journalism. Khairul Bashar (Executive Director, Aidcom) outlined the seminar’s goal: to offer a forum for senior journalists and media executives to exchange views, identify issues, and recommend methodologies for training in development journalism. The "Satellite Teleconferencing" session, which focussed on investigative qxxthg, featured an Asian panel of senior journalists and American journalists. This was organized with technical assistance from the United States Information Service. The Asian panelists were Philip Matthews, Mochtar Lubis, s. M. Ali, Gamsudin Rahim, and Islami Lustapa. American panelists were Bell Dedman and Jonathan Newman. This panel discussed investigative journalism as practiced in the United States and on sharing the norms followed in practicing the same skills in Asia. The panel on "Development Journalism: Challenges and Future Direction" was chaired by Haji A. Samad Ismail (Chairman, Panel of National Information Policy, Malaysia). Participants included Mochtar Lubis, S. M. Ali, Kadir Jasin (Group Editor, New Straits Z’imes, Malaysia), Abdul Rahman Sulaiman (Editor-in-Chief, Bernama [Malaysian News Agency]), Haji Mazlan Nordin (Chairman, Bernama), and Samsudin Abdul Rahim (Head, Communication Department, National University of Malaysia). The panel made the following points: development journalism should always portray changes that should be humanized; the process of adjust ...